2013
DOI: 10.3402/iee.v3i0.20450
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological hazard analysis of ready-to-eat meats processed at a food plant in Trinidad, West Indies

Abstract: BackgroundA bacteriological assessment of the environment and food products at different stages of processing was conducted during the manufacture of ready-to-eat (RTE) chicken franks, chicken bologna and bacon at a large meat processing plant in Trinidad, West Indies.MethodsSamples of air, surfaces (swabs), raw materials, and in-process and finished food products were collected during two separate visits for each product type and subjected to qualitative or quantitative analysis for bacterial zoonotic pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 29 publications
2
46
2
4
Order By: Relevance
“…It was reported that the hands of food handlers were implicated in 42% of foodborne outbreaks that occurred between 1975 and 1998 in the United States (Ayçiçek et al, 2004.). In a recent study (Syne et al, 2013) investigated the microbiological contamination in ready-to-eat food products processed at a large processing plant in Trinidad, West Indies, S. aureus was the most common pathogen detected. The overall prevalence of S. aureus detected in air, food, and environmental samples was 27.1% (46/170).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 2424-2431mentioning
confidence: 99%
“…It was reported that the hands of food handlers were implicated in 42% of foodborne outbreaks that occurred between 1975 and 1998 in the United States (Ayçiçek et al, 2004.). In a recent study (Syne et al, 2013) investigated the microbiological contamination in ready-to-eat food products processed at a large processing plant in Trinidad, West Indies, S. aureus was the most common pathogen detected. The overall prevalence of S. aureus detected in air, food, and environmental samples was 27.1% (46/170).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 2424-2431mentioning
confidence: 99%
“…As a rule, when RTE meat products reach the packaging environment in the plants, they should be free of harmful bacteria (Syne et al, 2013); however, the inherent risk of recontamination by L. monocytogenes in meat processing environments has been well documented and must be addressed (Gombas et al, 2003, Gómezet al, 2015.…”
Section: Sdrp Journal Of Food Science and Technologymentioning
confidence: 99%
“…In addition, air plays a significant role in the transmission of pathogens and may implicated in contamination of food at various stages of processing (Lues et al, 2007). Contamination of processed foods can occur due to poor water quality and unacceptable levels of airborne microorganisms in the processing environment (Syne et al, 2013). Microorganisms found in the form of bioaerosols may cause human health problems, such as allergies, and may impair the functions of the respiratory, immune and nervous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms found in the form of bioaerosols may cause human health problems, such as allergies, and may impair the functions of the respiratory, immune and nervous systems. Additionally, the presence of foodborne pathogens in poultry meat and meat products can result also in economic losses to producers due to recalls from market places (Syne et al, 2013).…”
Section: Introductionmentioning
confidence: 99%